Sex and Stroke in Thrombolyzed Patients and Controls. Issue 2 (February 2017) - Hametner, Christian; MacIsaac, Rachael L.; Kellert, Lars; Abdul-Rahim, Azmil H.; Ringleb, Peter A.; Lees, Kennedy R.; Alexandrov, A.; Bath, P.M.; Bluhmki, E.; Bornstein, N.; Chen, C.; Claesson, L.; et al.
Abstract : Background and Purpose—: We hypothesized that any sex-related difference in outcome poststroke is explained by other prognostic factors and that the response to intravenous recombinant tissue-type plasminogen activator (r-tPA) is equal in males and females after adjustment for such factors. Methods—: We accessed an independent collection of randomized clinical trials—the VISTA (Virtual International Stroke Trials Archive). Data were preprocessed by selecting complete cases (n=8028) and matching females to males (coarsened exact matching, n=4575, 24.3% r-tPA). Outcome was assessed by the 7-point modified Rankin Scale (mRS) measured at 90 days after ischemic stroke. Relationship among variables was estimated by adjusted regression analysis. Results—: In nonthrombolyzed patients, ordinal analysis of mRS adjusting for stroke- and sex-related prognostic factors suggested comparable outcomes for females and males (odds ratio, 0.96; 95% confidence interval, 0.85–1.06). Females responded comparably to r-tPA as did males, irrespective of the outcome definition of mRS (ordinal: P Interaction =0.46, relative excess risk because of interaction=0). The number needed to treat was 6.8 and 11.2 for 1 female to achieve mRS score of 0 to 2 and 0 to 1, which was highly congruent with males. Analysis for a nonlinear variation of age-by-sex revealed a good outcome for females <45 years with significant disadvantage thereafter (mRS score of 0–2: P Interaction =0.004). No relationship between sex, r-tPA, and bleeding complications was evident. Conclusions—: Functional outcome (mRS) without r-tPA was overall similar between the sexes, as was the response to r-tPA. Nonlinear sex-by-age interaction improved estimates of functional independence; this should be considered in sex-related studies in stroke. Abstract : Supplemental Digital Content is available in the text.